AJARAN AGAMA HINDU SEBAGAI PEDOMAN PEMBINAAN KERUKUNAN UMAT - I Gd Dedy Diana Putra (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2021)
The diversity in Indonesia is so complex that it can be seen from the existence of such diverse religions as Islam, Catholicism, Protestantism, Hinduism, Buddhism and Confucianism. In this regard, the hope to create kinship and harmony is a fundamental thing to be achieved by each religion. The starting point in carrying out religious life is to lead to an atmosphere of harmony. Talking about harmony, in fact it is not a new thing, because this presence is integrated with life in society and is largely determined by local situations and conditions. Each adherent of a good religion must live in harmony and peace. Therefore, inter-religious harmony is unlikely to be born from an attitude of blind fanaticism and an attitude of not caring about the rights of diversity and the feelings of others. Harmony between religious communities itself can also be interpreted as tolerance between religious communities. In tolerance itself, basically, people must be open-minded and accept differences between religious communities. In addition, the community must also respect each other, for example in terms of worship, between followers of one religion and another do not interfere with each other. Thus, inter-religious harmony is one of the main sticks in maintaining a good atmosphere, peaceful, not fighting, not moving, united in heart and agreeing between religious people of different religions to live in harmony. In the context of this harmony, the Hindu concept is contained simply in accordance with the instructions of Hindu religious teachings, both in the Vedic scriptures and Hindu literature. The sources of guidance for Hindu religious teachings in the context of religious life.